PERAN KEKUATAN CITRA MEREK DAN WORD OF MOUTH, DALAM KEPUTUSAN MEMILIH FOVERE HOTEL DI PALANGKA RAYA, INDONESIA - Nahan, Noorjaya; Abdi, Muhamad Ruzaini (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Community service in increasing the number of consumers through strategies in the field of marketing, is carried out as a strength for business actors. The activity was carried out quantitatively by applying a questionnaire assessment system to 100 consumers. Brand image is the company's main system in hotel management that is built to provide consumer trust value. In Palangka Raya, the Fovere hotel is a three-star hotel with various facilities for vacation to metting. So, the ability of business actors/hotel management to build a brand image by providing appropriate services to consumers is needed. In addition, the form of consumer satisfaction is to give recommendations to others with word of mouth. The results show that the brand image and WOM are very important in improving the decision to choose (purchase) at the Fovere hotel in Palangka Raya.